The Case for Knowledge Management Governance for Africa - Mchombu, Kingo (My University, 2010)
In organisational context KM refers to the totality of strategies aimed at creating smart organisations able to leverage knowledge from its various information and communication assets, to learn from past experiences whether bad or good and to create new value through knowledge (Menkhoff 2007). In other words, using knowledge as a strategic business resource
Keywords: ICADLA, conference, digital library, archive, knowledge management, Africa